(untitled) (Journal of Pharma Insights and Research, 2025)
Nigeria faces a critical public health challenge due to widespread antibiotic misuse, driven by misinformation and inadequate digital health literacy. The proliferation of social media platforms, online health forums, and unregulated digital pharmacies has created an environment where inaccurate health information spreads rapidly, leading to dangerous self-medication practices. Many Nigerians struggle to differentiate between credible medical sources and misleading online content, particularly regarding antibiotic use for viral infections. While digital platforms contribute to misinformation, they also present opportunities for effective health education when properly regulated. Mobile health applications, e-pharmacies, and social media channels can serve as valuable tools for promoting responsible antibiotic use. National eHealth initiatives, partnerships with social media companies, healthcare professional engagement, and culturally adapted education programs offer promising strategies to enhance digital health literacy. However, significant barriers persist, including limited internet access, language diversity, economic constraints, and distrust in formal healthcare systems. It is essential to overcome these challenges through policy reforms, digital inclusion programs, and educational curricula. Strengthening digital health literacy empowers individuals to evaluate online health information critically, reduce antibiotic misuse, and mitigate the growing threat of antimicrobial resistance in Nigeria